Exploring access to postpartum mental healthcare at a peri-urban community health centre: a socio-ecological perspective - Leshaba, Palesa (University of the Free State, 2025)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱 Postpartum mental health (PPMH) remains a neglected aspect of maternal care within South Africa's primary health care system. This neglect is especially evident in peri-urban areas where overburdened community health centres (CHCs) often lack the capacity to offer mental health support. Although national policy acknowledges the importance of maternal mental health , postpartum women continue to face significant barriers in accessing care. These challenges extend beyond resource limitations, and include stigma, inconsistent screening practices, and sociocultural norms that minimise emotional distress. As a result, symptoms of depression, anxiety, or trauma frequently go undetected in settings that prioritise physical health. Existing research has largely overlooked the complex multilevel factors shaping access to PPMH care. This study addresses this gap by examining the determinants of access to postpartum mental health services (PPMHS) at a peri-urban CHC in Gauteng Province in South Africa. 𝗠𝗲𝘁𝗵𝗼𝗱𝗼𝗹𝗼𝗴𝘆 The study employed a qualitative exploratory case study design grounded in a constructivist paradigm. The socio ecological model (SEM) provided a guiding framework to explore the multi-level determinants of access to PPMHS at the CHC across five levels: individual, interpersonal, organisational, community, and societal. Semi structured interviews were conducted with ten postpartum women (within six months of delivery) attending postnatal care at the CHC, as well as eight healthcare providers directly involved in maternal care. Participants were selected through purposive sampling to ensure depth and relevance of insights. Data were transcribed verbatim and analysed using abductive thematic analysis (ATA), which allowed for the integration of both data-driven themes and SEM-informed theoretical constructs. Ethical approval was obtained with all participants providing informed consent. Confidentiality and respectful engagement were upheld throughout the research process. 𝗙𝗶𝗻𝗱𝗶𝗻𝗴𝘀 The study identified a range of interrelated barriers and facilitators to accessing PPMHS across all five levels of the SEM. At the individual level, limited awareness of PPMH and internalised stigma discouraged help-seeking. In contrast, exposure to mental health education and trauma-informed care provided by healthcare providers facilitated service use. At the interpersonal level, emotional support from family members and partners played an instrumental role in enabling access to care. Conversely, the absence of such support posed a significant barrier. At the organisational level, systemic issues such as inconsistent screening practices, staff shortages, a lack of provider training in mental health, and the absence of mental health integration into routine postnatal care hindered access to PPHM services. However, access was supported by the availability of trained mental health professionals and proactive referral efforts by some healthcare providers. At the community level, entrenched cultural stigma, by rigid gender roles, and religious belief surrounding emotional distress inhibited disclosure and care seeking, yet respectful treatment and the use of culturally sensitive practices by healthcare providers improved acceptability of mental health services. At the societal level, limited involvement of frontline providers in policymaking and the absence of structured PPMH monitoring mechanisms weakened implementation of PPMHS at the CHC. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻 The study highlights the complex, layered factors that shape access to PPMH care at the CHC. Addressing these challenges requires a coordinated, multilevel response. Priorities should include strengthening mental health literacy among women and families, enabling family support, augmenting provider capacity through training, and incorporating culturally responsive care into routine care services at the CHC. It is also important to have meaningful involvement of frontline healthcare providers in policy development and the establishment of quantifiable implementation strategies. A context-sensitive and integrated approach to implementing PPMHs has the potential to strengthen maternal mental health outcomes and ensure that primary healthcare services are more responsive to the needs of postpartum women.
Dissertation(M.HS.(Health Systems Research & Development))--University of the Free State, 2025
Keywords: Postpartum mental health; Socio-ecological model; Community health centre; Postpartum period; Postpartum women; Healthcare provider